2008
DOI: 10.4314/ajhs.v14i3.30865
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study and audit of the spleen in Nigerians

Abstract: SUMMARYStudies on the spleen in Nigerians are rare. This study reviewed retrospectively the gross and histopathological findings in spleens received at the histopathology laboratory of the Obafemi Awolowo University Hospital (OAUTHC), Ile-Ife, Nigeria. 119 consecutive splenectomy specimens received within a period of 18 years were analysed with respect to age, sex, pathological diagnoses and indication for splenectomy. There were 76 males and 43 females with a mean age of 34.8 years (STD 19.6 years). Spleen we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
4
0
2
Order By: Relevance
“…The higher incidence in this age group may be related to greater predisposition to traumatic injury in this age group. The age and gender distribution are close to the reported series in the literature [3,8,9] . The most common histopathological findings in our study were haemorrhagic necrosis and capsular disruption as a result of splenic laceration in road traffic accidents and blunt trauma.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The higher incidence in this age group may be related to greater predisposition to traumatic injury in this age group. The age and gender distribution are close to the reported series in the literature [3,8,9] . The most common histopathological findings in our study were haemorrhagic necrosis and capsular disruption as a result of splenic laceration in road traffic accidents and blunt trauma.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, two specimens of traumatic rupture showed increased blackish brown pigments mimicking malarial pigments but definite malarial parasite could not be detected. In other studies predisposing factors like malaria, amyloidosis, follicular hyperplasia etc were detected in cases of ruptured spleen [3,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Ancak literatürde splenektomi materyallerinin klinikopatolojik özelliklerini konu alan az sayıda çalışma bulunmaktadır. Ülkeler arasında ve yaşa göre sırala-mada farklılıklar olmakla birlikte, en sık splenektomi endikasyonları arasında travmaya bağlı rüptür, hematolojik hastalıklar, infeksiyonlar ve batın içi diğer organ patolojileri nedeniyle uygulanan operasyonlarda prosedür gereği yapılanlar ilk sıralarda yer almaktadır (3,4,7,8) . Çalışmamızda da benzer durumlar splenektomi endikasyonlarının büyük çoğunluğunu oluşturmakta-dır.…”
Section: Discussionunclassified
“…Normal bir erişkinde dalak ortalama 150-200 g ağırlığında ve 12x7x3 cm boyutlarında-dır (1) . Abdomende bulunduğu lokalizasyon, anatomik olarak koruyucu bir kemik kafese sahip olmadığından travmalara sekonder incinmelere son derece yatkın-dır (3) . Splenektominin en sık endikasyonları arasında; derece 4-5 dalak travması, masif splenomegalisi olanlarda dalak büyüklüğüne ait semptomların kontrolü, dalağın kist ve tümörleri, hematolojik hastalıkların tanı ve tedavisi yer almaktadır (4) .…”
unclassified
“…Chemoprevention study on spleen was carried out because the spleen is the largest organ of the mononuclear phagocyte system and is involved in all systemic inflammation (Adelusola, Osasan, & Afolabi, 2008;Jiang, Ma, & Liu, 2018). The chemoprevention effect of C. aeruginosa on the spleen is an indicator how the active compound from the plant suppresse or prevents either the initial phases of carcinogenesis or the progression of cancer.…”
Section: Introductionmentioning
confidence: 99%